TiB2-based composite ceramic with high bending strength and preparation method thereof
By optimizing raw material formula and SPS process, combining heat treatment and water quenching, the problems of easy oxidation and brittleness of TiB2 ceramics at high temperatures are solved, significantly improving their bending strength, achieving efficient and economical performance improvement of the material, and being suitable for a wide range of Engineering applications.
Patent Information
- Application Number
- CN202411149992.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-21
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-08-21
AI Technical Summary
TiB2 ceramics are prone to oxidation in high temperature environments, have high brittleness, low bending strength, and have high cost, complex process and unstable effects, making them difficult to widely use in actual engineering environments.
By optimizing raw material formulation and discharge plasma sintering (SPS) process, combined with subsequent heat treatment and water quenching, a high bending strength TiB2 matrix composite ceramic is formed, which improves the density and microstructure uniformity of the material, and reduces grain growth and interface defects. .
It significantly improves the bending strength of TiB2 ceramics, which is increased by more than 50%, enhances the thermal stability and mechanical properties of the material, simplifies the process flow, reduces costs, and has good repeatability and scalability in industrial production.
Smart Images

Figure CN119191847A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of non-oxide structural ceramics, and in particular relates to a TiB2-based multiphase ceramic with high bending strength and a preparation method thereof. Background Art
[0002] Titanium diboride (TiB2) ceramics have shown broad application prospects in aerospace, military equipment, nuclear industry, and high-temperature structural materials due to their high melting point, high hardness, high electrical conductivity, and good chemical stability. However, despite its many excellent physical and chemical properties, it is brittle, has relatively low bending strength at room temperature and high temperature, and is prone to oxidation failure at high temperatures, which largely limits its application range and reliability in actual engineering environments.
[0003] In recent years, a lot of exploration has been done to improve the bending strength of TiB2 ceramics, including the introduction of second phase particles (such as SiC and Al2O3, etc.) to strengthen the matrix, and optimizing the microstructure by controlling the grain size and morphology. Although the above methods have improved the bending strength of TiB2 ceramics to a certain extent, they still face challenges such as high cost, complex process, and unstable effect. Therefore, developing a new method that is more economical and efficient, simple in process, and can significantly improve the bending strength of TiB2 ceramics is of great significance for promoting the application of such materials in a wider range of fields.
[0004] Existing TiB2 ceramics still have the following problems: 1. Thermal stability: Due to changes in the thermal expansion coefficient and high-temperature oxidation, the strength of TiB2 ceramics will be affected after use in a high-temperature environment, and the material is prone to cracking or failure. 2. Microstructure control: The microstructure of TiB2 ceramics, such as grain size, impurity content, phase distribution, etc., directly affects its strength. Finding a way to optimize these parameters to improve strength is a challenge. 3. Interface problems: There may be interface defects in TiB2 ceramics, such as grain boundary weakening, phase interface separation, etc. These problems will significantly reduce the bending strength of the material. 4. Influence of heat treatment: The heat treatment process has a great influence on the microstructure and properties of TiB2 ceramics. How to maintain or improve its strength during heat treatment is a problem that needs to be solved.
[0005] Based on the above problems, the present invention aims to effectively improve the bending strength of TiB2 ceramics through innovative material design and processing technology to meet the needs of modern engineering technology for high-performance ceramic materials. Summary of the invention
[0006] In view of the shortcomings of the prior art, the present invention aims to provide a TiB2-based composite ceramic with high bending strength and a preparation method thereof. The present invention significantly improves the bending strength of TiB2 ceramics by optimizing the raw material formula, controlling the spark plasma sintering (SPS) process and subsequent heat treatment, while ensuring other excellent properties.
[0007] To achieve the above object, the present invention is implemented by the following technical solutions:
[0008] The present invention provides a TiB2-based composite ceramic with high bending strength. The raw materials of the TiB2-based composite ceramic are selected from TiN powder, B4C powder, Si powder, Al powder, B powder, BN powder, TiB2 powder, AlN powder and SiC powder. The raw materials are mixed according to any one of the following chemical reaction equations (1) to (5):
[0009] 4TiN+3B4C+3Si=4TiB2+4BN+3SiC (1);
[0010] 4TiB2+4BN+3SiC=4TiB2+4BN+3SiC (2);
[0011] 3TiN+Al+8B+5.98BN=3TiB2+7.98BN+AlN (3);
[0012] 3TiB2+7.98BN+AlN=3TiB2+7.98BN+AlN (4);
[0013] 3TiN+Al+8B=3TiB2+2BN+AlN (5).
[0014] Preferably, the average particle size of the TiN powder is 0.5-10 μm, and the purity is greater than 95%; the average particle size of the B4C powder is 1-10 μm, and the purity is greater than 95%; the average particle size of the Si powder is 0.5-5 μm, and the purity is greater than 95%; the average particle size of the Al powder is 0.1-10 μm, and the purity is greater than 95%; the average particle size of the B powder is 0.2-10 μm, and the purity is ≥95%; the average particle size of the BN powder is 1-10 μm, and the purity is greater than 95%; the average particle size of the TiB2 powder is 0.2-10 μm, and the purity is greater than 95%; the average particle size of the AlN powder is 0.5-10 μm, and the purity is greater than 95%; the average particle size of the SiC powder is 0.2-10 μm, and the purity is greater than 95%. Further, the SiC powder is α-SiC powder.
[0015] In the above scheme, the selection of raw material powders with fine particle size and high purity can help reduce the porosity during the sintering process, thereby improving the density and mechanical properties of the final product. Raw material ratio: The raw material ratio is carried out according to the specific chemical reaction equations (1) to (5), which can ensure the formation of the desired TiB2-based composite ceramics. At the same time, the introduction of the second phase (such as SiC, AlN, etc.) can effectively improve the microstructure of TiB2 and enhance its mechanical properties.
[0016] The present invention also provides a method for preparing a TiB2-based composite ceramic with high bending strength, comprising:
[0017] Step 1, weighing raw material powder according to the ratio of the designed chemical reaction equation, and obtaining raw material powder required for sintering after preliminary treatment;
[0018] Step 2, pouring the raw material powder obtained in step 1 into a mold, and sintering it in a spark plasma sintering environment to obtain a sintered composite ceramic;
[0019] Step 3: heat-treating the composite ceramic obtained in step 2, and obtaining the desired TiB2-based composite ceramic after cooling.
[0020] Preferably, in step 1, the preliminary treatment method of the raw material powder is: adding the weighed raw material powder into a ball mill and mixing them evenly, using anhydrous ethanol and zirconium oxide balls as ball milling media, drying the powder after rotary evaporation in a vacuum drying oven, and grinding and sieving to obtain the raw material powder required for sintering.
[0021] Preferably, in step 2, the sintering temperature ranges from 1400°C to 1800°C.
[0022] Preferably, in step 2, the sintering heating rate is 100-200°C / min.
[0023] Preferably, in step 2, the sintering pressure is 30-60 MPa.
[0024] Preferably, in step 2, the sintering holding time is 5 to 20 minutes.
[0025] Preferably, in step 2, the inner wall of the mold and the raw material powder are separated by graphite paper.
[0026] Preferably, in step 3, the heat treatment method is: the heat treatment temperature is 800-1400°C, the insulation time is 10-120min, and immediately after the insulation is completed, it is immersed in 0-100°C water for 10-120min, and finally taken out of the water and naturally cooled.
[0027] The spark plasma sintering (SPS) process in the above scheme, sintering conditions: The SPS sintering process can quickly complete the sintering process at a lower temperature, avoiding the grain growth caused by long-term high temperature, which is conducive to the formation of a fine grain structure, thereby improving the bending strength of the material. Sintering pressure: Sintering at a pressure of 30 to 60 MPa helps to improve the density of the material and reduce the porosity, thereby further improving the mechanical properties of the material. Insulation time: A shorter insulation time (5 to 20 minutes) can reduce the chance of grain growth, maintain the fineness of the microstructure, and help improve the strength of the material. Although the above preparation process can obtain dense and uniformly refined TiB2-based composite ceramics, the strength of the material still needs to be improved.
[0028] The subsequent heat treatment and water quenching process in the above scheme, heat treatment temperature: heat treatment is carried out in the range of 800-1400°C in air atmosphere, which can promote the optimization of the microstructure inside the material and form a dense oxide layer on the surface of the material to bridge the microcracks; water quenching process: by rapidly immersing in distilled water for cooling, the appearance of a compressive stress zone under the surface oxide layer is conducive to significantly improving the strength of the material.
[0029] The technical solution provided by the present invention has the following beneficial effects:
[0030] 1. By optimizing the raw material formula and innovating the heat treatment process, a variety of TiB2-based composite ceramic systems are designed, providing a method for further improving the bending strength of TiB2 ceramics, which is crucial for improving the application performance of materials in extreme environments. The above-mentioned Examples 1-6 can obtain dense TiB2-based composite ceramics with refined grains, uniform microstructure, and no impurities; the grain boundaries are tightly bound, without obvious separation and weakening; the material maintains integrity after heat treatment and water quenching, the surface is relatively flat, there are no visible macro cracks or obvious shape degradation; compared with a single heat treatment process (Example 6), the micro defects on the surface and inside of the material are continuously bridged after water quenching, and the appearance of a compressive stress zone under the surface oxide layer is conducive to inhibiting the initiation and expansion of cracks during the transient water quenching process before the final failure, offsetting part of the thermal stress. Therefore, compared with the initial strength, the bending strength is continuously increased with the heat treatment temperature, and the maximum increase is more than 50% at 1400°C (Examples 1-5).
[0031] 2. Compared with other technologies, the present invention is a top-down strategy that can sinter and prepare ceramics with fine structures from coarse precursor powders. During the reaction, the particles can produce multiple nucleation sites, and the new particles formed by the reaction have higher sintering performance. Therefore, the densification of the material can usually be achieved at a temperature lower than the traditional hot pressing sintering temperature (lower than 200°C). In addition, by optimizing the heat treatment temperature and time, the oxidation and interface damage of TiB2 ceramics can be controlled, which helps to achieve the refinement of the microstructure of TiB2-based composite phase ceramic materials and the effective control of defects.
[0032] 3. The high-purity, cheap and easily available raw material powders can be mixed and then prepared into TiB2-based composite ceramics with refined grains through SPS. The raw materials are convenient and easy to obtain, and the preparation process, heat treatment and water quenching process are simple to operate, with a short cycle, and no sintering aids are required. It has good repeatability and scalability, which is conducive to the promotion and application of TiB2 ceramics in industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 The microscopic morphology of the sample sintered in Example 1;
[0034] Figure 2 This is the microscopic morphology of the sample of Example 1 after heat treatment at 1400°C;
[0035] Figure 3 This is the macroscopic morphology of the sample in Example 1 after heat treatment at 1400°C;
[0036] Figure 4 This is the microscopic morphology of the sample sintered in Example 2;
[0037] Figure 5 This is the microscopic morphology of the sample of Example 2 after heat treatment at 1000°C;
[0038] Figure 6 This is the macroscopic morphology of the sample of Example 2 after heat treatment at 1000°C;
[0039] Figure 7 This is the microscopic morphology of the sample sintered in Example 3;
[0040] Figure 8 This is the microscopic morphology of the sample of Example 3 after heat treatment at 1400°C;
[0041] Fig. 9 This is the macroscopic morphology of the sample in Example 3 after heat treatment at 1400°C. DETAILED DESCRIPTION
[0042] In order to enable those skilled in the art to better understand the technical solution of the present invention, the preferred implementation scheme of the present invention is described below in conjunction with specific embodiments, but it should not be understood as limiting the present invention and is only used as an example.
[0043] The experimental methods or test methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials are obtained from conventional commercial channels or prepared by conventional methods unless otherwise specified.
[0044] Example 1
[0045] TiN powder, B4C powder and Si powder are used as raw materials and are prepared according to equation (1).
[0046] The phase composition (volume content) of the obtained sample is 43% TiB2-26% SiC-31% BN.
[0047] Using anhydrous ethanol and zirconia balls as ball milling media, the three powders of TiN, B4C and Si according to the stoichiometric ratio are evenly mixed, then rotary evaporated, dried, ground and sieved, and finally poured into a graphite mold. The inner wall of the mold sleeve and the powder are separated by a 0.2mm thick graphite paper. The temperature is raised to 400℃, and the pressure applied to the sample is 40MPa. The sample is heated to 1700℃ at a rate of 100℃ / min and maintained at 1700℃ and 40MPa for 5min. Finally, the pressure is reduced to 3MPa and the heating is stopped. The sample is cooled to room temperature with the furnace. The relative density of the obtained ceramic is 98.1%, and the initial bending strength at room temperature is 521MPa. Several finely processed specimens (size: 2×2.5×25mm 3 ) were placed in a heating furnace at 800℃, 1000℃, 1200℃ and 1400℃ for 10 minutes, and then immediately immersed in 100℃ distilled water for 10 minutes. Finally, they were taken out of the water and placed in an area with good air circulation to cool naturally for 30 minutes. The strength of the final material after heat treatment at 800℃, 1000℃, 1200℃ and 1400℃ and water quenching was 597MPa, 647MPa, 681MPa and 733MPa, respectively, with a maximum increase of 40.6% (Table 1).
[0048] Figure 1 The microscopic morphology of the sample sintered in Example 1 is shown in FIG. Figure 2 This is the microscopic morphology of the sample in Example 1 after heat treatment at 1400°C. Figure 3 The macroscopic morphology of the sample in Example 1 after heat treatment at 1400°C is shown in Figure 1. Figure 1-Figure 3It can be seen that the dense and homogeneous TiB2-SiC-BN composite ceramics sintered at 1700℃ have significantly refined grains; the sample maintains integrity after heat treatment at 1400℃, with no visible macro cracks or obvious shape degradation; the surface is wrapped by a dense oxide film, presenting an island morphology of TiO2 particle aggregation, and the surface microcracks are repaired; the internal ceramic matrix is subjected to compressive stress from the surface oxide layer, and the strength is significantly improved.
[0049] Example 2
[0050] TiB2 powder, BN powder and SiC powder are used as raw materials and are prepared according to equation (2).
[0051] The phase composition (volume content) of the obtained sample is 43% TiB2-26% SiC-31% BN.
[0052] Using anhydrous ethanol and zirconia balls as ball milling media, the three powders of TiB2, BN and SiC according to the stoichiometric ratio are evenly mixed, then rotary evaporated, dried, ground and sieved, and finally poured into a graphite mold. The inner wall of the mold sleeve and the powder are separated by a 0.2mm thick graphite paper. The temperature is raised to 400℃, and the pressure applied to the sample is 60MPa. The sample is heated to 1800℃ at a rate of 100℃ / min and maintained at 1800℃ and 60MPa for 20min. Finally, the pressure is reduced to 3MPa and the heating is stopped. The sample is cooled to room temperature with the furnace. The relative density of the obtained ceramic is 98.5%, and the initial bending strength at room temperature is 457MPa. Several finely processed specimens (size: 2×2.5×25mm 3 ) were placed in a heating furnace at 800℃, 1000℃, 1200℃ and 1400℃ for 15 minutes, and then immediately immersed in 100℃ distilled water for 20 minutes. Finally, they were taken out of the water and placed in an area with good air circulation to cool naturally for 30 minutes. The strength of the final material after heat treatment at 800℃, 1000℃, 1200℃ and 1400℃ and water quenching was 502MPa, 541MPa, 602MPa and 659MPa, respectively, with a maximum increase of 44.2% (Table 1).
[0053] Figure 4 This is the microscopic morphology of the sample sintered in Example 2. Figure 5 This is the microscopic morphology of the sample in Example 2 after heat treatment at 1000°C. Figure 6 The macroscopic morphology of the sample in Example 2 after heat treatment at 1000°C is shown in Figure 2. Figure 4-Figure 6It can be seen that the dense and homogeneous TiB2-SiC-BN composite ceramics sintered at 1800℃ have no visible pores; the integrity of the sample is still maintained after heat treatment at 1000℃, the surface is relatively flat, and there is no obvious shape degradation; the surface is covered with a continuous oxide layer, which is beneficial to reduce the sensitivity of microcracks and repair microcracks.
[0054] Example 3
[0055] TiN powder, Al powder, B powder and BN powder are used as raw materials and are prepared according to equation (3).
[0056] The phase composition (volume content) of the obtained sample is 32% TiB2-8% AlN-60% BN.
[0057] Using anhydrous ethanol and zirconia balls as ball milling media, the four powders of TiN, Al, B and BN according to the stoichiometric ratio are evenly mixed, then rotary evaporated, dried, ground and sieved, and finally poured into a graphite mold. The inner wall of the mold sleeve and the powder are separated by a 0.2mm thick graphite paper. The temperature is raised to 400℃, and the pressure applied to the sample is 60MPa. The sample is heated to 1800℃ at a rate of 100℃ / min and maintained at 1800℃ and 60MPa for 20min. Finally, the pressure is reduced to 3MPa and the heating is stopped. The sample is cooled to room temperature with the furnace. The relative density of the obtained ceramic is 98.2%, and the initial bending strength at room temperature is 324MPa. Several finely processed specimens (size: 2×2.5×25mm 3 ) were placed in a heating furnace at 800℃, 1000℃, 1200℃ and 1400℃ for 15 minutes, and then immediately immersed in 100℃ distilled water for 20 minutes. Finally, they were taken out of the water and placed in an area with good air circulation to cool naturally for 30 minutes. The strength of the final material after heat treatment at 800℃, 1000℃, 1200℃ and 1400℃ and water quenching was 380MPa, 421MPa, 436MPa and 484MPa, respectively, with a maximum increase of 49.4% (Table 1).
[0058] Figure 7 This is the microscopic morphology of the sample sintered in Example 3. Figure 7 This is the microscopic morphology of the sample in Example 3 after heat treatment at 1400°C. Figure 7 The macroscopic morphology of the sample in Example 3 after heat treatment at 1400°C is shown in Figure 2. Figure 7-Figure 9 It can be seen that dense TiB2-AlN-BN composite ceramics can be obtained by sintering at 1800℃; the integrity of the sample is still maintained after heat treatment at 1400℃, and there is no obvious shape degradation; the surface is covered with dense and continuous needle-shaped oxide particles, which is conducive to bridging microcracks.
[0059] Example 4
[0060] TiB2 powder, AlN powder and BN powder are used as raw materials and are prepared according to equation (4).
[0061] The phase composition (volume content) of the obtained sample is 32% TiB2-8% AlN-60% BN.
[0062] Using anhydrous ethanol and zirconia balls as ball milling media, the three powders of TiB2, AlN and BN according to the stoichiometric ratio are evenly mixed, then rotary evaporated, dried, ground and sieved, and finally poured into a graphite mold. The inner wall of the mold sleeve and the powder are separated by a 0.2mm thick graphite paper. The temperature is raised to 400℃, and the pressure applied to the sample is 60MPa. The sample is heated to 1800℃ at a rate of 100℃ / min and maintained at 1800℃ and 60MPa for 20min. Finally, the pressure is reduced to 3MPa and the heating is stopped. The sample is cooled to room temperature with the furnace. The relative density of the obtained ceramic is 98.4%, and the initial bending strength at room temperature is 252MPa. Several finely processed specimens (size: 2×2.5×25mm 3 ) were placed in a heating furnace at 800℃, 1000℃, 1200℃ and 1400℃ for 15 minutes, and then immediately immersed in 100℃ distilled water for 10 minutes. Finally, they were taken out of the water and placed in an area with good air circulation to cool naturally for 30 minutes. The strength of the final material after heat treatment at 800℃, 1000℃, 1200℃ and 1400℃ and water quenching was 302MPa, 331MPa, 364MPa and 382MPa, respectively, with a maximum increase of 51.6% (Table 1).
[0063] Example 5
[0064] TiN powder, Al powder and B powder are used as raw materials and are prepared according to equation (5).
[0065] The phase composition (volume content) of the obtained sample is 56% TiB2-17% AlN-27% BN.
[0066] Using anhydrous ethanol and zirconia balls as ball milling media, the three powders of TiN, Al and B according to the stoichiometric ratio are evenly mixed, then rotary evaporated, dried, ground and sieved, and finally poured into a graphite mold. The inner wall of the mold sleeve and the powder are separated by a 0.2mm thick graphite paper. The temperature is raised to 400℃, and the pressure applied to the sample is 40MPa. The sample is heated to 1800℃ at a rate of 100℃ / min and maintained at 1800℃ and 40MPa for 20min. Finally, the pressure is reduced to 3MPa and the heating is stopped. The sample is cooled to room temperature with the furnace. The relative density of the obtained ceramic is 98.4%, and the initial bending strength at room temperature is 412MPa. Several finely processed specimens (size: 2×2.5×25mm 3 ) were placed in a heating furnace at 800℃, 1000℃, 1200℃ and 1400℃ for 15 minutes, and then immediately immersed in 80℃ distilled water for 15 minutes. Finally, they were taken out of the water and placed in an area with good air circulation to cool naturally for 30 minutes. The strength of the final material after heat treatment at 800℃, 1000℃, 1200℃ and 1400℃ and water quenching was 495MPa, 515MPa, 530MPa and 594MPa, respectively, with a maximum increase of 44.2% (Table 1).
[0067] Example 6
[0068] TiN powder, B4C powder and Si powder are used as raw materials and are prepared according to equation (1).
[0069] The phase composition (volume content) of the obtained sample is 43% TiB2-26% SiC-31% BN.
[0070] Using anhydrous ethanol and zirconia balls as ball milling media, the three powders of TiN, B4C and Si according to the stoichiometric ratio are evenly mixed, then rotary evaporated, dried, ground and sieved, and finally poured into a graphite mold. The inner wall of the mold sleeve and the powder are separated by a 0.2mm thick graphite paper. The temperature is raised to 400℃, and the pressure applied to the sample is 60MPa. The sample is heated to 1800℃ at a rate of 100℃ / min and maintained at 1800℃ and 60MPa for 5min. Finally, the pressure is reduced to 3MPa and the heating is stopped. The sample is cooled to room temperature with the furnace. The relative density of the obtained ceramic is 98.9%, and the initial bending strength at room temperature is 543MPa. Several finely processed specimens (size: 2×2.5×25mm 3) were placed in a heating furnace at 800℃, 1000℃, 1200℃ and 1400℃ for 10 minutes, and then the samples were taken out and placed in an area with good air circulation to cool naturally for 30 minutes. The strength of the final material after heat treatment at 800℃, 1000℃, 1200℃ and 1400℃ was 503MPa, 485MPa, 425MPa and 302MPa, respectively, with a maximum reduction of 44.4% (Table 1).
[0071] According to the TiB2-based composite ceramics prepared in the above embodiment, no obvious cracks and shape degradation were found on the surface of the samples after heat treatment at different temperatures, and the bending strength is shown in the following Table 1:
[0072] Table 1
[0073]
[0074]
[0075] As can be seen from Table 1 above, a single heat treatment process will cause the bending strength of the material to decrease continuously with temperature (Example 6), while heat treatment combined with water quenching (Examples 1-5) will increase the strength of the material continuously with the heat treatment temperature, with a maximum increase of more than 50% at 1400°C.
[0076] The above are only preferred embodiments of the present invention. It should be noted that the above preferred embodiments should not be regarded as limiting the present invention, and the protection scope of the present invention should be based on the scope defined by the claims. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the spirit and scope of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.
Claims
1. A TiB2-based composite ceramic with high bending strength, characterized in that: The raw materials of the TiB2-based composite ceramic are selected from TiN powder, B4C powder, Si powder, Al powder, B powder, BN powder, TiB2 powder, AlN powder and SiC powder, and the raw materials are mixed according to any one of the following chemical reaction equations (1) to (5): 4TiN+3B4C+3Si=4TiB2+4BN+3SiC (1); 4TiB2+4BN+3SiC=4TiB2+4BN+3SiC (2); 3TiN+Al+8B+5.98BN=3TiB2+7.98BN+AlN (3); 3TiB2+7.98BN+AlN=3TiB2+7.98BN+AlN (4); 3TiN+Al+8B=3TiB2+2BN+AlN (5).
2. The TiB2-based composite ceramic with high bending strength according to claim 1, characterized in that: The average particle size of the TiN powder is 0.5-10μm, and the purity is >95%; the average particle size of the B4C powder is 1-10μm, and the purity is >95%; the average particle size of the Si powder is 0.5-5μm, and the purity is >95%; the average particle size of the Al powder is 0.1-10μm, and the purity is >95%; the average particle size of the B powder is 0.2-10μm, and the purity is ≥95%; the average particle size of the BN powder is 1-10μm, and the purity is >95%; the average particle size of the TiB2 powder is 0.2-10μm, and the purity is >95%; the average particle size of the AlN powder is 0.5-10μm, and the purity is >95%; the average particle size of the SiC powder is 0.2-10μm, and the purity is >95%.
3. A method for preparing a TiB2-based composite ceramic with high bending strength as claimed in claim 1 or 2, characterized in that: include: Step 1, weighing raw material powder according to the ratio of the designed chemical reaction equation, and obtaining raw material powder required for sintering after preliminary treatment; Step 2, pouring the raw material powder obtained in step 1 into a mold, and sintering it in a spark plasma sintering environment to obtain a sintered composite ceramic; Step 3: heat-treating the composite ceramic obtained in step 2, and obtaining the desired TiB2-based composite ceramic after cooling.
4. The method for preparing the TiB2-based composite ceramic with high bending strength according to claim 3, characterized in that: In step 1, the preliminary treatment method of the raw material powder is: the weighed raw material powder is added into a ball mill and mixed evenly, anhydrous ethanol and zirconium oxide balls are used as ball milling media, the powder after rotary evaporation is dried in a vacuum drying oven, and then ground and sieved to obtain the raw material powder required for sintering.
5. The method for preparing the TiB2-based composite ceramic with high bending strength according to claim 3, characterized in that: In the step 2, the sintering temperature ranges from 1400°C to 1800°C.
6. The method for preparing the TiB2-based composite ceramic with high bending strength according to claim 3, characterized in that: In the step 2, the sintering heating rate is 100-200°C / min.
7. The method for preparing the TiB2-based composite ceramic with high bending strength according to claim 3, characterized in that: In the step 2, the sintering pressure is 30-60 MPa.
8. The method for preparing the TiB2-based composite ceramic with high bending strength according to claim 3, characterized in that: In the step 2, the sintering holding time is 5 to 20 minutes.
9. The method for preparing the TiB2-based composite ceramic with high bending strength according to claim 3, characterized in that: In the step 2, the inner wall of the mold and the raw material powder are separated by graphite paper.
10. The method for preparing the TiB2-based composite ceramic with high bending strength according to claim 3, characterized in that: In step 3, the heat treatment method is: the heat treatment temperature is 800-1400°C, the insulation time is 10-120min, and immediately after the insulation is completed, it is immersed in 20-100°C water for 10-120min, and finally taken out of the water and naturally cooled.
Citation Information
Patent Citations
Multi-element diphase ceramic material used for conductive crucible and preparation method thereof
CN101265107A
Zirconiumdiboride-graphite ceramic matrix composite material and preparation method thereof
CN102010205A
In-situ multiphase mixed-scale ceramic reinforced Al-Zn-Mg-Cu aluminium alloy in melt and preparation method thereof
CN109576526A
Method for preparing component-adjustable BN-containing multiphase ceramic through reactive sintering
CN114133250A
Thermal-shock-resistant antioxidant Si3N4 ceramic and preparation method thereof
CN121758182A
Cited By
B4c surface oxide layer, preparation method thereof and b4c-based modified ceramic
CN122749176A